SAPS/SAID revisited: A causal relation to the substorm current wedge. Issue 8 (26th August 2017) - Mishin, Evgeny; Nishimura, Yukitoshi; Foster, John
Abstract: We present multispacecraft observations of enhanced flow/electric field channels in the inner magnetosphere and conjugate subauroral ionosphere, i.e., subauroral polarization streams (SAPS) near dusk and subauroral ion drifts (SAID) near midnight. The channels collocate with ring current (RC) injections lagging the onset of substorms by a few to ∼20 min, i.e., significantly shorter than the gradient‐curvature drift time of tens of keV ions. The time lag is of the order of the propagation time of reconnection‐injected hot plasma jets to the premidnight plasmasphere and the substorm current wedge (SCW) to dusk. The observations confirm and expand on the previous results on the SAID features that negate the paradigm of voltage and current generators. Fast‐time duskside SAPS/RC injections appear intimately related to a two‐loop circuit of the substorm current wedge (SCW2L). We suggest that the poleward electric field inherent in the SCW2L circuit, which demands closure of the Region 1 and Region 2 sense field‐aligned currents via meridional currents, is the ultimate cause of fast RC injections and SAPS on the duskside. Key Points: SAPS/RC injections on the duskside appear in much shorter time than predicted by the ion gradient‐curvature drift Duskside SAPS and RC injections are causally related to the substorm current wedge two‐loop current system SAID/SAPS channel is an integral part of the turbulent plasmasphere boundary layer